2011
DOI: 10.1089/gyn.2009.0104
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Infections and Adverse Pregnancy Outcomes: The Oral Health—Fetal Connection

Abstract: Objective: The increasing awareness of the relationship between maternal oral health and adverse pregnancy outcomes is well documented in the dental literature.The present review aims at summing up the current state of evidence and research on the same and sharing the available literature with the obstetric and other general practitioners so that the patients are diagnosed and treated with an interdisciplinary approach. Materials and methods: A search of the dental literature, including Medline Ò =PubMed throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Similar results were found in Saudi Arabia in 2015 (Al‐Swuailem, 2015 ), where 91.1% were unaware of the link between periodontal disease and preterm birth. In India in 2015 (Sajjan et al, 2015 ) and 2013 (Avula et al, 2013 ), 78% did not know that periodontal disease is common during pregnancy, 66% had no knowledge about periodontal disease, and 87.2% had never heard of the link between oral health and adverse pregnancy outcomes. In China in 2015 (Zhong et al, 2015 ), pregnant women were found to be unaware that dental check‐ups (37%) during the second trimester (18%) were preventive measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found in Saudi Arabia in 2015 (Al‐Swuailem, 2015 ), where 91.1% were unaware of the link between periodontal disease and preterm birth. In India in 2015 (Sajjan et al, 2015 ) and 2013 (Avula et al, 2013 ), 78% did not know that periodontal disease is common during pregnancy, 66% had no knowledge about periodontal disease, and 87.2% had never heard of the link between oral health and adverse pregnancy outcomes. In China in 2015 (Zhong et al, 2015 ), pregnant women were found to be unaware that dental check‐ups (37%) during the second trimester (18%) were preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia in 2013 (George et al, 2013b ), only 10% of women surveyed received information about oral health care during pregnancy through pamphlets, antenatal care and dentists. In contrast, India in 2013 (Avula et al, 2013 ) and Kuwait in 2005 (Honkala & Al‐Ansari, 2005 ) reported that no pregnant women were referred to a dentist or received information about oral health care during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia in 2013 (26), only 10% of the women evaluated received information about oral health care during pregnancy through brochures, prenatal care and dentists. In contrast, India in 2013 (19) and Kuwait in 2005 (27) reported that no pregnant woman was referred to dentistry by gynecologists or received information about oral care during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…During prolonged periodontal inflammation, periodontal pathogens and related virulence factors not only invade the periodontal tissues but can also disseminate throughout different systemic organs [9]. Thus, important periodontal pathogens have been detected in the placentas of women with preeclampsia [13] and in the amniotic fluid of pregnant women with a diagnosis of premature labor [66] or premature labor with intact membranes [14,16]. …”
Section: Discussionmentioning
confidence: 99%